JURIDICAL DYNAMICS BETWEEN FREEDOM OF DIGITAL EXPRESSION AND DEFAMATION OFFENSES: A CASE STUDY OF MEME MAKING GOVERNMENT OFFICIALS IN THE PERSPECTIVE OF LAW NUMBER 1 OF 2024 - Anshari Sembiring, M Fauzan; Fitria Br. Hutapea, Syahira; Feraliya Tinambunan, Fingky; Stevani Siburian, Aprilia; Aqil Sulistiyo, Ahmad; Pika Lumban Batu, Dewi (JOURNAL EQUITABLE, 2026)
This study examines the juridical dynamics between the protection of digital freedom of expression and the enforcement of defamation offenses, with a focus on the creation of internet memes that target government officials. The formulation of the problem in this study centers on the legal limitations of political satire and the potential criminalization of social criticism in cyberspace. The research method used is normative juridical with a legislative approach and a conceptual approach, utilizing primary and secondary legal materials including analysis of the meme case of Bahlil Lahadalia and ITB students. The results of the study show that Law Number 1 of 2024 has accommodated escape devices through Article 45 paragraph (7) which excludes criminal sanctions if the act is carried out in the public interest or criticism. Nevertheless, inconsistencies and ambiguities in interpretation at the level of law enforcement officials on digital visual culture products still occur, so that it has the potential to trigger a chilling effect that threatens the constitutional rights of citizens. This study concludes the need for standard and strict interpretation guidelines for law enforcement officials in order to realize substantive justice